PREPARATION AND CHARACTERIZATION OF TI(IV) OXIDE GRAFTED ONTO SILICA ON A SILICA-GEL SURFACE - Kubota, L. T.; Gushikem, Y.; Decastro, S.; Moreira, J. C. (Elsevier B.V., 1991)
Silica gel with a surface area of 500 m2g-1 and an average pore diameter of 60 angstrom was chemically modified with Ti(IV) oxide using the grafting method. The amount of metal oxide attached to the surface was 1.8.10(-3) mol g-1. The X-ray photoelectron spectra showed that the metal ion species on the surface are Ti(IV) in TiO2 and MTiO3 (M = Ca2+, Sr2+, Ba2+ and Pb2+), i.e. they have the binding energy of Ti2p3/2 = 458.7 eV. The dehydration of the solid at higher temperature increased the O(II)/Ti (O(II) = oxygen bound to titanium atom) ratio, presumably due to a reticulation of the hydrous Ti(IV) oxide on the silica surface at higher temperatures. Migration of Ti(IV) into the silica gel matrix was observed but the specific surface area was not significantly changed.